Relating Individual Differences in Reading Skill to Neural Indices of Proactive Control and Online Filtering During a Working Memory Task. Issue 5 (3rd July 2021) - Mottarella, Malayka; Yamasaki, Brianna L.; Prat, Chantel S.
ABSTRACT: Individual differences in reading skill have frequently been related to variability in working memory capacity; however, it is unclear what drives this relation. The present study investigated two attentional control mechanisms that may contribute to this relation: proactive control and online filtering. To examine how the neural mechanisms of these processes relate to individual differences in reading, functional magnetic resonance imaging (fMRI) data collected during a novel working memory paradigm was correlated with measures of reading skill. Results indicated that skilled readers deployed greater proactive control resources, as evidenced by more activation in left anterior prefrontal regions, when cued proactively about task-relevant features than less-skilled readers. Additionally, high-vocabulary individuals showed online filtering benefits. These findings provide novel contributions to our understanding about the relation between working memory and reading and suggest that proactive control and attentional filtering mechanisms may play a key role in driving this relation.